Synthesis, Characterization, Cellular Uptake, and In Vitro Anticancer Activity of Fullerenol-Doxorubicin Conjugates - Xu, Beihua; Yuan, Li; Hu, Ying; Xu, Zhiyuan; Qin, Jiang-Jiang; Cheng, Xiang-Dong (Frontiers in Pharmacology, 2021)
Doxorubicin (DOX) is one of the most commonly used chemotherapeutic agents for treating human cancer. However, its clinical use has been limited by DOX-induced cardiotoxicity as well as other side effects. In the present study, we designed and synthesized the fullerenol (FU)-DOX conjugates and folic acid (FA)-grafted FU-DOX conjugates for improving the selectivity and activity of DOX in cancer cells. We further characterized the physicochemical properties and examined the release kinetics, cellular uptake, and in vitro anticancer activities of FU-DOX and FA-FU-DOX. The results showed that FU-DOX and FA-FU-DOX had a mean diameter of <200 nm and a low polydispersity. Both FU-DOX and FA-FU-DOX exhibited pH sensitivity and their DOX release rates were higher at pH 5.9 versus pH 7.4. The cellular uptake studies indicated that FU conjugation enhanced the intracellular accumulation of DOX in human hepatocellular carcinoma (HCC) cell lines (BEL-7402 and HepG2) and the immortalized normal human hepatocytes (L02). The conjugation of FA to FU-DOX further promoted the drug internalization in an FR-dependent manner and enhanced the cytotoxicity against HCC cells. In conclusion, the newly prepared FA-FU-DOX conjugates can optimize the safety and efficacy profile of DOX.